WHO OVERSEES JUSTICE? CRIMINAL REVIEW AS AN EXPRESSION OF THE OPACITY AND INEFFECTIVENESS OF JUDICIAL REFORMS IN BRAZIL - Antonio de Souza Saraiva, Luiz; Fernandes da Rocha Solano, Wládia; de Sousa Albuquerque, Dalva; Victor Andrade Souza, João; Souto Filho, Wilton; Endrenw da Cunha Silva, Naun; Rayra Lopes Paula, Rhanna; Fernandes da Rocha Solano, Kaio; Gizelle Teles Alves, Luiza; Magalhães Medeiros Ibiapina, Helaine (Revista Gênero e Interdisciplinaridade, 2026)
The Brazilian criminal justice system faces significant obstacles related to judicial errors, wrongful convictions, and difficulties in reviewing criminal sentences. Although criminal review is provided for in national legislation, its effectiveness is often limited in practice. In this context, creating an autonomous body with specific authority to oversee and reassess convictions emerges as an alternative capable of strengthening legal certainty and reducing injustices resulting from procedural or evidentiary flaws. This study, developed through a literature review, legislative analysis, and comparison with international experiences, investigates the feasibility and relevance of establishing such a body in Brazil. The central question is whether an independent oversight entity could contribute to a fairer and more efficient system in identifying and correcting judicial errors. The study concludes that implementing a specialized criminal review body would represent a significant advancement in improving the criminal justice system, aligning it with the principles of the Democratic Rule of Law and enhancing protection against wrongful convictions.